The Madman and Psychotherapy in the Neoliberal Academy : A Chinese Doctoral Student's Experience in the United States - Zhang, Jing (Journal of International Students, 2022)
This self-reflective paper examines my experience as a Chinese doctoral student while studying in a large research university in America. Through my self-reflection, with Foucault's analysis on power, I hope to shed some light on my experience with the neoliberal academy, which caused much discomfort and created my fragmented identities. Instead of questioning the problematic neoliberal power relations that caused my discomfort in the first place, as the madman of higher ed, I was directed to psychotherapy to treat my symptoms, which only caused more confusion. Through my story, I hope to reveal how social context, Neoliberalism in this case, and social discourse of psychotherapy, work hand in hand in higher education space, which have exercised intangible power and created the fragmented identities among many international doctoral students in America. At the end of the paper, I also provided suggestions for graduate students to navigate the neoliberal academy.